STRATEGI LANGSUNG KESANTUNAN TINDAK DIREKTIF GURU TAMAN KANAK-KANAK - Anisa Ulfah (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2020)
The kindergarten students tend to learn by imitating people behavior andlanguage hence the teacher itself must use polite and understandable language as statedin the standard academic qualifications and competence for kindergarten teacher.Politeness in language is closely related to the social norm in particular society. Thus thegoal of this research is to describe a teachers’ direct politeness in kindergarten that focuson politeness strategy function of politeness. This study used qualitatif method in the formof language research by using socio pragmatics. In collecting the data, the researcherwas an observer. The data of this research was in the form of data form, strategy and theteacher’s function in direct politeness accompanied by recording session in the learningactivities in the class. According to data analysis, it was found a description politeness inkindergarden teacher that was explained in politeness strategy covered (1) direct strategywithout politeness and (2) direct strategy with politeness covered. Based on the findings,the reseacher makes a conclusions is the use of direct strategy often regarded as lesspolite is often used by the teacher due to increase learning interaction.